Pengaruh Model Pembelajaran Stimulating Higher Order Thinking Skills terhadap Keterampilan Berpikir Kritis Siswa Kelas V pada Pembelajaran IPAS - Salma Khoirunnisa Fithri; Fadilah Nur Sugiyanto (Jurnal Inovasi Pendidikan Dan Pembelajaran, 2026)
This research is motivated by the low critical thinking skills of students in science learning with an average of 50.18% in the low category. This is caused by the habit of learning that still uses low cognitive level questions (C1-C3), so it has not trained high cognitive level critical thinking skills (C4-C6). This study aims to: 1) Determine the differences in students' critical thinking skills before and after using the inquiry model in the control class. 2) Determine the differences in students' critical thinking skills before and after using the Stim-HOTS learning model in the experimental class. 3) Determine the effect of the Stim-HOTS learning model on students' critical thinking skills. This study uses a quantitative approach with a quasi-experimental method and a nonequivalent control group pretest-posttest design. The research subjects consisted of 29 students of class VA as the control class and 27 students of class VB as the experimental class at MIM Gonilan Kartasura, which were determined through cluster random sampling techniques. The research instruments were essay tests, syntax implementation observation sheets, and documentation. The results of the study showed that 1) There were differences in students' critical thinking skills before and after using the inquiry model in the control class. 2) There is a difference in critical thinking skills before and after using the Stim-HOTS model in the experimental class. 3) There is an influence of the Stim-HOTS learning model on students' critical thinking skills with a sig value (2-tailed) of 0.002 < 0.05.